Identificacao e mapeamento de areas de maior eficiencia fotossintetica para a cana-de-acucar - Garcia, G. J.; Teixeira, A. L A; Gerardi, L. H O (My University, 1989)
The objective was the study of better areas for sugar cane exploitation, using variables related to the classes and exposition of slopes, edaphic and climatic variables. Data were analysed with the aid of a Geographic Information System supported by 8 bit microcomputer, and maps of North exposition, photosynthetically the most efficient, were produced for different gradients of slope. These maps combined with traditional maps can be a very helpful tool to planners. -from English summary
Identification and mapping of areas of better photosynthetic efficiency for sugar cane
Keywords: agricultural planning; GIS; mapping technique; photosynthetic efficiency; slope orientation; sugar cane